NETWORKED JOURNALISM: PELUANG KOLABORATIF JURNALIS DAN AKTIVIS ERA DIGITAL - Stepanus Bo’do’ (Journal of Urban Sociology, 2021)
Digital technology has increased the interest of student activists engaging in journalistic activities. To participate in collaborative news production in the digital age, they need a better understanding of journalism, both conceptually and practically. Conceptually, to understand the new structure of journalism formed by digital networks. Practically, to recognize how the horizontal structure of the digital network opens equal and collaborative opportunities for professional journalists and non-journalist actors. Literature studies on scientific publications using the keyword “networked journalism” indicate opportunities for student activists to become non-journalistic actors, who can be involved in news production and become actors who act as programmers or switchers in networked communicative power in the digital era.Keywords: Networked Journalism, Collaborative Opportunities, Journalists, Digital Age